Meredam Konflik Dengan Pembentukan Dan Pengembangan Social Capital - Mulyadi, Deddy (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2005)
Social capital is a set of values or norms informally shared by a group of people that enable them to cooperate with each other. The social capital which is built and developed in a society allows the people to do their social functions effectively and redeems any social conflicts happened at a certain scale. In Indonesia, for example, the society has large defisit of social capital, which was built within colonial and feodal policies. The defisits are reflected in the way the people live, in which the grow a dishamony, live in fear and distrust of each other. Therefore, it is a collective responsibility that the people do a socio-cultural transformation towards a stronger and healthier social capital.